Pengaruh Impowering Leadership, Perceived Organizational Support, Dan Work Life Balance Terhadap Kinerja Karyawan (Pada Karyawan Bandar Udara Sultan Muhammad Salahuddin Bima Nusa Tenggara Barat) - Fikriansyah, M.; Sunaryo, Hadi; Rahman, Fahrurrozi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The purpose of this study is: 1) To test the information content of Impowering Leadership, Perceived Organizational Support and Work Life Balance on Employee Performance at Sultan Muhammad Salahuddin Bima Airport. 2) To determine the effect of Impowering Leadership, Perceived Organizational Support and Work Life Balance on Employee Performance at Sultan Muhammad Salahuddin Bima Airport.The sample in this study amounted to 37 people who were employees of Sultan Muhammad Salahuddin Bima Airport. The sampling technique used was purposive sampling. The data used in the study used primary and secondary data. Based on the results of the analysis that has been carried out that each question item in the research questionnaire is normally distributed and there are no problems with the results of the simultaneous test which states that the results of the variables Impowering Leadership, Perceived Organizational Support, and Work Life Balance, simultaneously have a significant effect on Employee Performance at Sultan Muhammad Salahuddin Bima Airport. Keywords: Impowering Leadership, Perceived Organizational Support, Work Life Balance, Employee Performance.